Effects of metformin and cinnamon on 1,5 anhydroglucitol, adiponectin and ghrelin on newly diagnosed type 2 diabetes mellitus patients - Mohammad, Shatha; Fadhil, Nabeel; Mahmood, Mohammad (Jordan Medical Journal, 2021)
Backgrounds and Aims: Cinnamon, is one of the commonly used herbs for T2DM in spite of variable evidence. This study aimed to show the effect of cinnamon when combined with metformin on the glycemic marker; serum 1,5 anhydroglucitol, and the metabolic syndrome markers; adiponectin and ghrelin, in newly diagnosed type 2 diabetes mellitus patients.Materials and Methods: This is a randomized controlled trial study that has been conducted over 12 weeks. It included 57 males and females who were, 32-60-year-old. States that may affect the results were excluded. Group 1 patients (n. 30) were treated with metformin alone (500 mg) three times daily. Group 2 patients (n. 27) were treated with metformin 500mg three times daily and cinnamon, 3capsules per day (each capsule contained 1000 mg of crude cinnamon powder) for 12 weeks. A control group of apparently healthy subjects were used for comparing the results.Results: Metformin group showed a significant rise in 1.5AG level (p 0.028) and an insignificant rise in ghrelin and adiponectin levels. However, the metformin plus cinnamon group showed a significant rise in 1,5AG (0.017) and ghrelin (p 0.041) and a highly significant rise in adiponecting level (p value 0.009) that approached the control group level.Conclusion: adding, crude cinnamon to metformin produced significant improvement in 1,5anhydroglucitol and ghrelin levels and highly significant improvement in adiponectin level, suggesting that crude cinnamon is a beneficial adjunctive therapy in treating T2DM and metabolic syndrome.Key words: 1,5 anhydroglucitol, Adiponectin, Cinnamon, Ghrelin, Metformin